PENGARUH KOMPETENSI MANAJERIAL DAN MOTIVASI BERPRESTASI TERHADAP KOMPETENSI PROFESIONAL GURU MADRASAH ALIYAH NEGERI PONTIANAK - Fatimah, Siti; Sukmawati, Sukmawati; Chiar, M. (Universitas Tanjungpura, 2021)
AbstractThe aimed of this research are to find out the influence of principal Islamic State SeniorHigh School in Pontianak for managerial competences and achievement motivation forprofessional teachers